Máquinas de cena contemporâneas : Urbitária e a materialização da escritura cênica em Cidade dos Outros - Horevicht, Tatiana Mendes (2014)
This paperlooks at howUrbitária, machinescenespectacleOtherCities, CiaStaffTheatre-MTcombinesscenery,scenic area andmaterializes thescripturescenicspectacle. Toassist in understanding theconcept ofscenic areaand sceneryworkwithCiroDelNero andFranciscoJavier. Alsothe understandingthedramaturgyof EugenioBarbaanddramatografyof João Brites. The appearance of the stage machinesaspolysemicobjectsthat contribute tothetheatrical showdramaturgyislatestincontemporary theaterand isproposingthe theater groupTheBand, directed byJoãoBritesin Palmela-PT.